Study on Cochlear Implants (CIs) and Plasticity of the Auditory System - Gabr, Takwa A. (New Frontiers in Medicine and Medical Research Vol. 12, 2021)
Cochlear implants (CIs) represent very successful solution in severe to profound hearing loss. However, the outcome of CIs show great variability among cochlear implantees. Central factors are important contributors to the success despite of the peripheral factors play an important role. The great variability in CIs outcomes might be related to auditory plasticity. The appropriate auditory inputs are crucial for central auditory development either through natural or electrical hearing. Hearing deprivation has drastic effect on central auditory function in contrary to hearing restoration through CIs which has positive central impact and proper communication and perception.